PENDEKATAN PER SE ILLEGAL DAN RULE OF REASON DALAM HUKUM PERSAINGAN (PERBANDINGAN INDONESIA-MALAYSIA) - Hanif Nur Widhiyanti (Arena Hukum)
Abstract Approach to the nature of illegal per se and rule of reason prohibition has long been applied in determining whether an act hinder competition or not. Competition law of Indonesia and Malaysia also implement a ban properties per se illegal or rule of reason, but did not mention explicitly in the formulation of laws and regulations. The unfirm arrangement model imposes a difficult responsibility for institution of business competition authorities to be able to precisely define the reference as a measure that should be used in assessing an anti-competitive act. This research is a normative law with legislation approach and comparative law. From the discussion, it was concluded that the application of the nature of illegal per se and rule of reason prohibition in Law No. 5 of 1999 and the Competition Act 2010 of Malaysia implemented through an assessment of how the result level of an anti-competitive actions capable of distorting the market and blocking, thus eliminating competition completely. Consideration was also made based on the alignment between normative rules in the Act with the basic theory of competition itself. Thus, the rule of law in the enforcement of competition law can be maintained. Key words: competition, per se illegal, rule of reasons